2007
DOI: 10.1037/0021-9010.92.2.410
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal deviance, organizational deviance, and their common correlates: A review and meta-analysis.

Abstract: Interpersonal deviance (ID) and organizational deviance (OD) are highly correlated (R. S. Dalal, 2005). This, together with other empirical and theoretical evidence, calls into question the separability of ID and OD. As a further investigation into their separability, relationships among ID, OD, and their common correlates were meta-analyzed. ID and OD were highly correlated (rho = .62) but had differential relationships with key Big Five variables and organizational citizenship behaviors, which lends support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

86
1,115
7
30

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,125 publications
(1,238 citation statements)
references
References 54 publications
86
1,115
7
30
Order By: Relevance
“…High-quality treatment by a manager signals that a staff member has status and is held in high esteem in the workplace (Thau et al, 2013). Fair treatment is of particular significance according to the findings of various studies, which have confirmed that workplace treatment has far-reaching consequences for both employees and the organisation when it comes to the following: civility (Pearson, Andersson & Porath, 2005); job satisfaction (Hasan, 2010); organisational citizenship behaviours (Rego & Cunha, 2010); quality of work life (Moghimi, Kazemi & Samiie, 2012); turnover (Muzumdar, 2011); work behaviours (Le Roy, Bastounis & Minibas-Poussard, 2012); interpersonal and organisational deviance (Berry, Ones & Sackett, 2007); and workplace aggression (Hershcovis, Turner, Barling, Inness, LeBlanc, Arnold et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…High-quality treatment by a manager signals that a staff member has status and is held in high esteem in the workplace (Thau et al, 2013). Fair treatment is of particular significance according to the findings of various studies, which have confirmed that workplace treatment has far-reaching consequences for both employees and the organisation when it comes to the following: civility (Pearson, Andersson & Porath, 2005); job satisfaction (Hasan, 2010); organisational citizenship behaviours (Rego & Cunha, 2010); quality of work life (Moghimi, Kazemi & Samiie, 2012); turnover (Muzumdar, 2011); work behaviours (Le Roy, Bastounis & Minibas-Poussard, 2012); interpersonal and organisational deviance (Berry, Ones & Sackett, 2007); and workplace aggression (Hershcovis, Turner, Barling, Inness, LeBlanc, Arnold et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These indicate both constructs can be good predictors of performance, taking into account potential moderating effects (e.g., participants' occupation; Vinchur, Schippmann, Switzer & Roth, 1998). Several meta-analyses focusing on the personality domain have examined predictive validities for more specific criterion constructs than OJP, such as organizational citizenship behavior (Chiaburu, Oh, Berry, Li & Gardner, 2011;Hurtz & Donovan, 2000), job dedication (Dudley, Orvis, Lebiecki & Cortina, 2006) or counterproductive work behavior (Berry, Ones & Sackett, 2007;Dudley et al, 2006;Salgado, 2002). Hogan and Holland (2003) investigated whether differentiating the criterion-domain into two performance dimensions (getting along and getting ahead) impacts on predictive validities of personality constructs, using the Hogan Personality Inventory for a series of meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Triggering factors increase insecurity, thereby making it more likely for harassment processes to actually evolve. Organizational changes such as a change in management, restructuring and downsizing are examples of such factors 7 . Similarly, Heloani and Barreto 19 consider that it is possible to point out some of the organizational situations that facilitate the emergence of violent, abusive and humiliating behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…According to Nielsen et al 2 psychological harassment, refers to the mistreatment of workers of a nonphysical nature and has been conceptualized with a wide range of labels in the scientific literature, including abusive supervision 3 , incivility 4 , bullying/mobbing 5 , victimization 6 , interpersonal deviance 7 , emotional abuse 8 , ostracism 9 , and social undermining 10 , among others. It has been argued that this proliferation of constructs has led to a confusing state of affairs in which many scholars are studying virtually identical forms of mistreatment of subordinates and fellow workers, but with different terminology 2,11,12 .…”
Section: Introductionmentioning
confidence: 99%